Application of the Bacterial Meningitis Score for Infants Aged 0 to 60 Days. (10th December 2018) - Rees, Chris A; Cruz, Andrea T; Freedman, Stephen B; Mahajan, Prashant; Uspal, Neil G; Okada, Pamela; Aronson, Paul L; Thompson, Amy D; Ishimine, Paul T; Schmidt, Suzanne M; Kuppermann, Nathan; Nigrovic, Lise E; et al.
Abstract: In 4292 infants aged ≤60 days with cerebrospinal fluid (CSF) pleocytosis, the bacterial meningitis score had excellent sensitivity (121 of 121 [100.0%] [95% confidence interval, 96.5%–100.0%]) but low specificity (66 of 4171 [1.6%] [95% confidence interval, 1.3%–2.0%]) and therefore should not be applied clinically to infants in this age group.